An Archaeology of African and German Interactions at Adaklu-Waya, Volta Region - Amedekey, B. (university of Ghana, 2018)
The nineteenth century saw the scramble for territories in Africa by European powers. Germany a front-runner in this agendum employed several means in asserting their ideologies on the colonized. The joint activity of missionaries, administrators and merchants ensured that the colonized adopted German ideologies. One of the main reasons for the colonization of territories was economical, however; missionization was used as an overture to change the world views of the colonized. This was done to make it easy for the implementation of their plans. The Germans in their attempt to colonize territories were met with opposition at some places (e.g. Kete Krachi) and welcomed by others (e.g. Adaklu-Waya and Amedzofe). Missionization was an important factor in the German colonization process. The subject of German colonialism and missionary activities has been studied extensively historically and now archaeologically. This study investigated the German (Bremen) and African interactions at Adaklu-Waya. The research elucidates the interactions between the German missionaries and the Adaklu-Waya community. Ethnographic and material data gathered were reconciled with the documented accounts. Also, the study reveals the elements that influenced the interaction between the period 1855 and 1914 when the Germans left the country. Both the emic and etic perspectives were considered to help understand what transpired between the locals and the missionaries. Oral and documentary accounts, as well as the archaeological data, proved beyond doubt that there was contact with Germans at Adaklu-Waya. There was contact with other European countries such as England, France, and the Czekoslovakia. Significant changes were experienced as a result of the contact with Germans, however, this contact did not lead to a complete change in the existing ways of life of the people.
MA.
Keywords: Archaeology; German; Adaklu-Waya; Volta Region